(untitled) (Global Journal of Human-Social Science, 2013)
Behaviours in organizations can either be adjudged to be unethical and even criminal or being above board. Criminal and unethical issues are one of the most difficult to handle in organizations; and they pervade all levels and activities in the organisation. Specifically however, this article examines and discusses the following critical criminal and unethical concerns which include corruption, misuse of organizational assets, and false or misleading advertizing in organizations. The data were collected through secondary sources. The article concludes that, human resource manager’s and or organisation’s ability to tackle and control these ethical concerns is very important in keeping the organizations healthy and competitive; otherwise the organizations will suffer enormous setback, sometimes risk failure and even attract criminal action.